Foliar application of either melatonin or sodium nitpoprusside regulates the antioxidant status, and the morpho-physiological attributes and essential oil production in sage (Salvia officinalis L.) under salinity stress - Sheikhalipour, Morteza; Kulak, Muhittin; Mohammadi, Seyed Abolghasem; Esmaielpour, Behrooz; Nouraein, Mojtaba; Koçak, Mehmet Zeki; Farajzadeh, Seyed Mohammad; Gohari, Gholamreza; Fotopoulos, Vasileios; Vita, Federico (My University, 2024)
Soil salinity is one of the most severe abiotic stress factors affecting crop growth and yield. Among the molecules used to mitigate the adverse effects of salt, melatonin (MT) and the nitric oxide donor sodium nitroprusside (SNP) played a crucial role in mediating plant responses to salt stress. However, the molecules are worthy of further consideration and investigation with regard to the secondary metabolism of plants suffering from salt stress. Herein, the potential role of MT and SNP in alleviating/buffering the negative effects of salt stress on sage (Salvia officinalis L.) seedlings was investigated. In this context, MT (0, 50 µM, and 100 µM) and SNP (0, 50 µM, and 100 µM) were applied individually. The interactive effects of each molecule with salt stress (50 and 100 mM NaCl) were assessed using a range of morpho-physiological, biochemical and analytical parameters of sage. The results of the study showed that high salinity (100 mM NaCl) critically reduced growth and photosynthetic traits and increased oxidative stress damage parameters. On the other hand, high concentrations (100 µM) of MT or SNP treatments significantly improved growth, enhanced photosynthetic traits and mitigated oxidative stress damage parameters. For instance, individual treatments of both MT and SNP enhanced tolerance of sage against salinity stress by increasing relative water content, proline, total carbohydrates, total phenolics and flavonoid content, and the antioxidant enzymes and DPPH scavenging activities. Essential oil yield and individual essential oil compounds were also increased by MT and SNP. Overall, these molecules can be considered as potential protective agents against salinity stress in sage seedlings.
Keywords: Abiotic stress; Essential oil; Medicinal plants; Oxidative stress; Signal molecules